2019
DOI: 10.5539/jas.v11n8p31
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Meta Frontier Analysis of Smallholder Rice Farmers’ Technical Efficiency

Abstract: The aim of this study is to compare the technical efficiency of System of Rice Intensification (SRI) and Conventional Rice Production System (CRPS) farmers in Mali. Using cross-sectional data for 208 randomly selected rice farmers, the Stochastic Meta Frontier model is applied. The results indicate that the mean technical efficiency is 0.96 and 0.79 for SRI and CRPS respectively. This implies that SRI farmers were more technically efficiency than their counterpart. Similarly, the mean technology gap ratio was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
(27 reference statements)
2
11
0
Order By: Relevance
“…This study uses Huang et al's [40] stochastic meta-frontier model applied in Ng'ombe [22] and Mariko et al [23] to estimate the optimal output potentials of the rice farming industry in Awka North of Anambra State, Nigeria. The meta-frontier is used to investigate the TE of rice producers facing different production functions in the study area.…”
Section: Stochastic Meta-frontier Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…This study uses Huang et al's [40] stochastic meta-frontier model applied in Ng'ombe [22] and Mariko et al [23] to estimate the optimal output potentials of the rice farming industry in Awka North of Anambra State, Nigeria. The meta-frontier is used to investigate the TE of rice producers facing different production functions in the study area.…”
Section: Stochastic Meta-frontier Analysismentioning
confidence: 99%
“…For example, a descriptive study by Umar et al [18] examined how entrepreneurship and innovation by farmers improve lowland rice farming in Mattiro Ade, Patampanua District, Pinrang Regency, and South Sulawesi Province. Another study by Mariko et al [23] compared the TE of a system of rice intensification (SRI) and conventional rice production system (CRPS) in Mali by applying SMF techniques. Mariko et al [23] found that mean TE was 0.96 and 0.79 for SRI and CRPS, respectively, while the mean TGR was 0.98 and 0.91 for SRI and CRPS, respectively, with industrial TE averaging 0.858.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of yields per hectare, a relevant number of studies carried out in the country have shown that the paddy rice productivity at the farm-level is still low in Côte d'Ivoire [1][2][3][4][5]. The national paddy yield is 2.3 t ha −1 for all paddy rice production systems combined [3], while the average yields per hectare in some sub-region countries such as Mali range from 5.6 t ha −1 to 6.7 t ha −1 [6]. Although paddy rice production increases over the years, this increase is less proportional than the area cultivated.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with some countries in Sub-Saharan africa, the national yield average of paddy rice, which is estimated at 2.3 t/ha, remains low (Saito et al, 2019). For instance, Mariko et al (2019) report a rice yield ranging from 5.6 t/ha to 6.7 t/ha in Mali.…”
mentioning
confidence: 97%